Effect of The Ratio of H-Zeolite Catalyst and Temperature in The Opening Ring Reaction in Bio Lube Base Oil Production from Palm Oil - Izzan, Abdillah Iman; Octaviani, Ary; Purwanto, Purwanto (Universitas Diponegoro, 2020)
Lubricants are materials that can reduce friction between two components. Lubricants are very important to keep the engine from being damaged quickly. Currently lubricants on the market generally comes from petroleum derivatives with limited availability. Therefore, technology needs to be developed to look for other raw materials as a substitute for petroleum based lubricating oil, namely by utilizing the potential of existing vegetable oils, one of which is palm oil. Biolubricant made from palm oil will be made using the method of transesterification, epoxidation and ring opening reaction. To increase yield and high product quality, a catalyst in the form of H-Zeolite is used. So that this study aims to determine the effect of the ratio of H-Zeolite catalyst to ring opening reactions. The quality of lube base oil could be indicated from density, viscosity index and acid number. Acid number will smaller in presence higher content in 10% weight ratio of H-Zeolite as catalyst and EPOME also higher temperature of ring-opening reaction because the catalyst H-Zeolit will work more effective in temperature 75oC. Other evidence is of density and viscosity index would show good value than smaller amount of H-Zeolit and lower temperature of reaction. Advices for the future research are the purification needs to be done not only physically but also chemically to maximize the results obtained. Preferably on the reaction of opening the epoxides rings used a long chain alcohol compounds that have a high viscosity and boiling point to obtain a better viscosities value